Molecular prevalence, spatial distribution and epidemiological risk factors of Plasmodium knowlesi infection among Macaca fascicularis raffles in Peninsular Malaysia - Shahar, Zarith Suraya (2019)
Malaria caused by the haemoparasite Plasmodium is one of the important vector-borne tropical diseases among humans and a wide variety of animals, especially in the tropical regions where the mosquito vectors are abundant. Plasmodium knowlesi is a zoonotic simian malaria parasite with the Long-tailed macaques (Macaca fascicularis) are the natural reservoir hosts. It is now the most common and most fatal human malaria and is responsible for the increasing number of human malaria cases in Malaysia. Despite of the growing importance of zoonotic malaria, many aspects of its biology and epidemiology especially in the natural macaque hosts remains undetermined throughout Southeast Asia. The aim of this study was to ascertain the molecular prevalence, spatial distribution pattern, and epidemiological risk factors associated with P. knowlesi infection among Long-tailed macaques (Macaca fascicularis) in Peninsular Malaysia. Blood samples from 1587 Long-tailed macaques captured from 122 different locations in Peninsular Malaysia were subjected to Plasmodium detection by nested PCR amplification using primers targeting the 18S SSU rRNA gene. Molecular detection revealed that 48.39% of the macaques were positive for Plasmodium infection where P. cynomolgi was the most prevalent (28.92%), followed by P. inui (22.94%), P. coatneyi (14.37%) and P. knowlesi (13.55%). Analysis of Plasmodium species co-infection with P. knowlesi revealed a higher prevalence of multiple species infection (18.10%) compared to single P. knowlesi infection (9.90%). The multivariate regression analysis showed that number of Plasmodium species co-infection, gender of the macaques, spatial sampling zones and geographical location were the significant risk factors associated with P. knowlesi infection among the macaques. The spatial distribution pattern of P. knowlesi infection demonstrated that the highest infection occurred in the North-west zone and West-coastal region of Peninsular Malaysia, with numerous infection hotspots having >75% infection rates. Plasmodium knowlesi infection among the macaques was present in all states of Peninsular Malaysia indicating the endemicity and widespread nature of the infection. The overall analysis on the influence of host factors on the prevalence of P. knowlesi demonstrated that the prevalence rate was higher in the adult and juvenile macaques. The macaques sampled from the forest habitat recorded the lowest infection rate (11.1%) compared to those captured from the urban (14.79%), sub-urban (14.08%) and plantation (14.67%) habitats. However, this suggested that P. knowlesi infection is not restricted to the macaque in forest area but is also common among macaques inhabiting the urban, sub-urban and plantation areas. Higher prevalence of infection was also noted for the macaques sampled in habitats further away from the coast (>60km) and those inhabiting the inland at higher elevations (>80m above sea level). The present study constitutes the first attempt in Southeast Asia to screen a large number of macaques and to determine the epidemiological risk factors for P. knowlesi infection among the sylvatic macaque hosts. It is envisaged that the findings from this study will provide a better understanding on the molecular epidemiology and spatial distribution of this zoonotic parasite in this country and facilitate further surveillance and control programs to be initiated.